DEVELOPMENT OF SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF LISINOPRIL IN TABLET DOSAGE FORM - Nataliya Shulyak; Kateryna Budzivula; Lubomyr Kryskiw; Tetiana Kucher (Acta Medica Leopoliensia)
Aim. The research aims at developing a fast, simple, reliable spectrophotometric method according to "green" chemistry principles for the determination of lisinopril in pure substance and in drugs presented on the Ukrainian market.